Legal Approach and Tax Policy in E-commerce Transactions in the Middle of Digital Transformation - Refangga, Galih Setyo; Arifin, Rosyid; Suryaningsih, Suryaningsih; Suryapuspita, Merintha (PT FORMOSA CENDEKIA GLOBAL, 2024)
E-commerce provides numerous benefits for merchants and consumers alike, thus necessitating the continued use of the internet for transactions. However, it is anticipated that transactions following this model will eventually be supplanted by traditional face-to-face exchanges between buyers and sellers. The research methodology employed in this work is a normative legal approach. An review of tax laws regarding e-commerce transactions in Indonesia reveals that the growth of the Internet in the business sector, particularly in trade, not only provides several advantages for both buyers and sellers. E-commerce refers to the commercial transactions involving the purchase and sale of products and services conducted through the internet. The exponential growth of e-commerce in Indonesia has given rise to tax issues with e-commerce transactions.